Multi-residue Determination of Polar Veterinary Drugs in Livestock and Fishery Products by Liquid Chromatography/Tandem Mass Spectrometry. (27th November 2019) - Kanda, Maki; Nakajima, Takayuki; Hayashi, Hiroshi; Hashimoto, Tsuneo; Kanai, Setsuko; Nagano, Chieko; Matsushima, Yoko; Tateishi, Yukinari; Yoshikawa, Soichi; Tsuruoka, Yumi; Sasamoto, Takeo; Takano, Ichiro
Abstract: Residues of 37 polar veterinary drugs belonging to six families (quinolones, tetracyclines, macrolides, lincosamides, sulfonamides, and others) in livestock and fishery products were determined using a validated LC-MS/MS method. There were two key points insample preparation. First, extraction was performed with two solutions of different polarity. Highly polar compounds were initiallyextracted with Na2 EDTA-McIlvaine's buffer (pH 7.0). Medium polar compounds were then extracted from the same samples with acetonitrile containing 0.1% formic acid. Secondly, cleanup was performed using a single SPE polymercartridge. The first extracted solution was applied to the cartridge. Highly polar compounds were retained on the cartridge. Then, the second extracted solution was applied to the same cartridge. Both highly and medium polar compounds were eluted from the cartridge. This method satisfied the guideline criteria for 37 out of 37 drugs in swine muscle, chicken muscle, bovine muscle, prawn, salmon trout, red sea bream, milk, and honey; 35 out of 37 in egg; and 34 out of 37 in flounder. The LOQ ranged from 0.1 to 5 μg/kg. Residues were detected in 24 out of 110 samples and analyzed using the validated method.